Anti-NMDA Receptor Encephalitis in a Patient with Previous Psychosis and Neurological Abnormalities: A Diagnostic Challenge - R. David Heekin; Maria C. Catalano; Alfred T. Frontera; Glenn Catalano (Case Reports in Psychiatry)
Anti-N-methyl-D-aspartate (NMDA) receptor encephalitis is an autoimmune disorder characterized by IgG autoantibodies directed against the NR1 subunit of the NMDA glutamate receptor. Psychiatric symptoms are common and include psychosis, mania, depressed mood, aggression, and speech abnormalities. Neurological symptoms such as seizures, decreased responsiveness, dyskinesias, and other movement abnormalities and/or autonomic instability are frequently seen as well. We present the case of a woman who was followed up at our facility for over 14 years for the treatment of multiple neuropsychiatric symptoms. Initially, she presented with paresthesias, memory loss, and manic symptoms. Nine years later, she presented to our facility again, this time with left sided numbness, left eyelid droop, and word finding difficulties. Finally, five years later, she presented with manic symptoms, hallucinations, and memory impairment. During her hospitalization, she subsequently developed catatonic symptoms and seizures. During her stay, it was discovered that she was positive for anti-NMDA receptor antibodies and her symptoms responded well to appropriate therapy. This case demonstrates that it may be useful for clinicians to consider screening for anti-NMDA receptor antibodies in long-term patients with neuropsychiatric symptoms that have not adequately responded to therapy.